(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2023)
TORCH is an acronym made up of the first letters of the most common infections that are very dangerous for the fetus. TORCH infection is a group of infections that can affect people of any age and gender, but only occurs in pregnant women, fetuses and newborns. It is an infectious disease that mainly occurs during pregnancy and affects newborns. It produces the same pathological symptoms in men and women. This infection can be transmitted sexually, through airborne droplets, through mother’s milk to the child, through infection in the birth canal, and through the fur and feces of cats. affects the development of dementia. When an infected person coughs or sneezes, it can spread to other people through saliva and mucus. Early detection, treatment and prevention of all diseases included in the TORCH group is an effective measure for disease prevention.